EFFECT OF ANGIOTENSIN CONVERTING ENZYME INHIBITORCAPTOPRILAND SELECTIVE ß1-ADRENERGIC RECEPTORSBLOCKER ATENOLOL ON PROTEINURIA IN HYPERTENSIVEDIABETIC PATIENTS - Hassan, Suad (Iraqi Journal of Science, 2024)
Diabetes mellitus is one of the common health problems. It has many seriouscomplications among them are hypertension and diabetic nephropathy which maylead to renal failure. The first sign of early stage renal of failure or diabeticnephropathy is proteinuria which {presence of an abnormal amount of protein inurine} which leads to hypertension. As its known that hypertensive patients needtreatment and those with diabetes and proteinuria need more attention to be givenduring choosing their antihypertensive medications by using effective drugs withless side effects and comply with many aspects that are looked for by both thephysician and the patient. This study was conducted on {28} diabetic patients usinginsulin for treatment , those patients were newly diagnosed to have hypertension as acomplication of diabetes. The medications that are used as antihypertensive for themare either angiotensin converting enzyme inhibitorsACEI or Atenololtenormin.According to the antihypertensive drugs used for treatment they were classified intotwo groups :Group-A- ACEI patients, and group-B- Atenolol patients. The aim of this study wasto find whether Atenolol has an effect on proteinuria or not and to compare thiseffect if any with ACEI, despite the fact that ACEI has a renoprotective effect onkidney but because Atenolol became widely used for the management ofhypertension whatever the aetiology of hypertension. As it is known well that forevery medication there are side effects some of them might be serious so Atenololneeded to be used cautiously in diabetic patients because it causes masking ofhypoglycemia in addition to other side effects but its widely used by our physiciansin diabetic patients so we want to demonstrate here whether it has an effect on thelevel of proteinuria which might be a cause, or a result of hypertension in diabeticpatients, in order to decrease the unwanted side effects on those patients and to paymore attention during choosing the medications used for such patients. Therefore{24} hour urine was collected for each patient and total protein in urine wasmeasured before starting treatment and after different periods from usingmedications, in addition to monitor blood pressure and blood glucose levels.Fromthe results obtained it was clear that ACEI still the effective drug, it significantly( p < 0.05) lowers both blood pressure and the level of proteinuria in contrast toAtenolol which was not significant in lowering the level of proteinuria buteffectively lowered blood pressure .It was concluded that ACEI still the best to be the first choice medication fordiabetic hypertensive patients, while Atenolol needs more attention and follow upfor the patients when its decided to be used.